Negotiating Santri Identity in Electoral Politics: Political Image Construction in the 2024 Indonesian Election - Siti Fathonah; Rhesa Zuhriya Briyan Pratiwi; Ulfa Fauzia Argestya (Khazanah Sosial, 2025)
This article aims to describe the construction of the political identity of the santri community in the context of the 2024 General Election, highlighting the increasing visibility and influence of santri figures in Indonesia’s political landscape. This research adopts a qualitative descriptive approach. Data were collected through in-depth interviews, observation, and documentation, using snowball and purposive sampling techniques to select santri political figures who participated in the 2024 legislative elections. The validity of the data was ensured through source triangulation, and analysis was conducted using an interactive model involving data reduction, presentation, and verification. The findings reveal that santri political figures construct and display their identity—rooted in pesantren affiliation, kinship ties, and organizational networks—as strategic representations to gain political legitimacy. The research identifies three dominant identity patterns: traditional pesantren-based santri, Muslim intellectuals with academic backgrounds, and Nahdlatul Ulama (NU)-affiliated santri activists. These identities are performed through campaign activities, media engagement, and symbolic religious attributes. These findings contribute to the expanding discourse on religion and politics in Indonesia, particularly the strategic role of religious identity in political branding. The study offers practical insights for political practitioners and enriches scholarly understanding of identity construction within Islamic communities. Its originality lies in mapping santri political identity construction during a contemporary national election, an area underexplored in previous studies.